Jacob Baldes Batrachomyomachia Homeri Tuba Romana cantata (1637) und der Dreißigjährige Krieg - Werle, Dirk; Worms, Katharina (Scientia poetica, 2018)
One of the most extensive texts of the neolatin poet and Jesuit Jacob Balde is his ›Battle of the Frogs and Mice‹, a Latin version of the Batrachomyomachia, an ancient Greek epic, which for a long time was seen as a work of the founder of European literature, Homer. The pseudo-Homeric Batrachomyomachia was read as a humorous travesty of the Iliad. By assigning the comic text to Homer, scholars implied the appealing, yet wrongful idea that the author of the greatest mythical war was mocking his own work, thereby parodying the respectable genre of heroic epics. With Balde’s creation of a new version of this Greek poem during the Thirty Years’ War, the question arises as to whether his text is no more than an intertextual play on a famous literary genre, or whether it reacts to the recent historical events in early modern Europe - or both.